2016
DOI: 10.1039/c5cc08156d
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous BaSnO3 layer based perovskite solar cells

Abstract: One of the limitations of TiO2 based perovskite solar cells is the poor electron mobility of TiO2. Here, perovskite oxide BaSnO3 is used as a replacement. It has a higher electron mobility and the same perovskite structure as the light harvesting materials. After optimization, devices based on BaSnO3 showed the best performance of 12.3% vs. 11.1% for TiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 38 publications
(37 reference statements)
1
82
0
1
Order By: Relevance
“…It is worth noting, however, that research efforts towards the development of one-dimensional organic semiconductors are being made through techniques such as solution-phase synthesis, templating, electrospinning, and nanolithography [65]. TiO 2 , ZnO, SnO 2 , and WO x are the most commonly used materials (energy level diagram shown in Figure 5) for 1D-ETLs, although other inorganic semiconductors exist that could potentially be used in a one-dimensional nanostructure, such as Zn 2 SnO 4 [66], BaSnO 3 [67], and SrTiO 3 [68]. While not a focus of this review, common organic electron transport materials include fullerenes, methanofullerenes, and perylene derivatives.…”
Section: Materials For One Dimensional Electron Transport Layersmentioning
confidence: 99%
“…It is worth noting, however, that research efforts towards the development of one-dimensional organic semiconductors are being made through techniques such as solution-phase synthesis, templating, electrospinning, and nanolithography [65]. TiO 2 , ZnO, SnO 2 , and WO x are the most commonly used materials (energy level diagram shown in Figure 5) for 1D-ETLs, although other inorganic semiconductors exist that could potentially be used in a one-dimensional nanostructure, such as Zn 2 SnO 4 [66], BaSnO 3 [67], and SrTiO 3 [68]. While not a focus of this review, common organic electron transport materials include fullerenes, methanofullerenes, and perylene derivatives.…”
Section: Materials For One Dimensional Electron Transport Layersmentioning
confidence: 99%
“…Although these areas have great potential, there are only limited reports (129)(130)(131)(132)(133). We summarize recent research in the Supplemental Text.…”
Section: Solar Cells and Photoconductorsmentioning
confidence: 99%
“…The performance of the PSC fabricated with these ETL materials are summarized in Table 1 BaSnO3 and SrTiO3 are transparent semiconducting perovskite oxides with the same perovskite structure as MAPbI3. Zhu et al [24] and Bera et al [25] explored BaSnO3 and SrTiO3 as the replacement of TiO2 in MPSCs, respectively. Both of them found that the alternative scaffold affected the crystal growth and morphology of perovskite.…”
Section: Methodsmentioning
confidence: 99%